Leadership in Action : Issues and Observations - Two Ways About it - Learning to Deal with Ambiguity - Prince, Don (Center for Creative Leadership, 2002)
Because even with ambiguity, one thing is certain: in today's increasingly complex, perpetually changing, ever-more-diverse world, life and work will get only more ambiguous.